Improving Population Administration Services in Surabaya City: The Opportunities and Challenges of “Lontong Balap” Innovation - Noviyanti, Noviyanti; Ningrum Nungraina Lintang Alfrida, Tiara; Kunto Wibisono, Haryo; Arlupi Utami, Dian (REFORMASI, 2025)
The government of Surabaya City initiated the ‘Lontong Balap’ innovation to address various complaints in population administration documents that require a district court decision. It is a collaboration between the local government and the Surabaya District Court. This study analyses the opportunities and challenges of ‘Lontong Balap’ innovation as a good model of population administration services. It is descriptive qualitative research with data collection through in-depth interviews, observation, and documentation from the Population and Civil Registration officers in Surabaya, the Surabaya District Court, and applicants. It was conducted at the Surabaya District Court and Siola Mall Public Service. Data analysis was carried out using Miles Huberman technique through data collection, data reduction, presentation, and conclusion drawing. The results showed the opportunities of population administration services, including awareness, skills, and abilities of Surabaya District Court officers, organizational support from both agencies, and adequate facilities and infrastructure. On the other hand, the challenges come from the bureaucratic structure, such as negligence of officers from urban villages and the Population and Civil Registration of Surabaya, and the differences in court quotas. There are also barriers from outside the public sector, such as public doubts and various problems experienced by applicants.Pemerintah Kota Surabaya menginisiasi inovasi ‘Lontong Balap’ untuk mengatasi berbagai keluhan dalam dokumen administrasi kependudukan yang memerlukan putusan pengadilan negeri. Inovasi ini merupakan kerja sama antara pemerintah daerah dan Pengadilan Negeri Surabaya. Penelitian ini menganalisis peluang dan tantangan inovasi ‘Lontong Balap’ sebagai model layanan administrasi kependudukan yang baik. Penelitian ini merupakan penelitian kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi dari petugas Kependudukan dan Pencatatan Sipil di Surabaya, Pengadilan Negeri Surabaya, dan pemohon. Penelitian ini dilakukan di Pengadilan Negeri Surabaya dan Pelayanan Publik Siola Mall. Analisis data dilakukan dengan teknik Miles Huberman melalui pengumpulan data, reduksi data, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan peluang layanan administrasi kependudukan, meliputi kesadaran, keterampilan, dan kemampuan petugas Pengadilan Negeri Surabaya, dukungan organisasi dari kedua instansi, serta sarana dan prasarana yang memadai. Di sisi lain, tantangan berasal dari struktur birokrasi, seperti kelalaian petugas dari kelurahan dan Dinas Kependudukan dan Pencatatan Sipil Surabaya, serta perbedaan kuota pengadilan. Terdapat pula hambatan dari luar sektor publik, seperti keraguan publik dan berbagai permasalahan yang dialami oleh para pemohon.